2021
DOI: 10.1002/1873-3468.14261
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of γ‐glutamyl‐cysteine with intracellular and extracellular glutathione metabolic enzymes

Abstract: Gamma-glutamyl-cysteine (c-EC) is a precursor of glutathione (GSH) biosynthesis. We investigated whether it functions as a substrate for three intracellular and one extracellular GSH metabolic enzymes, which mediate the antioxidant defence function of GSH. Among them, glutathione peroxidase, glutathione S-transferase and c-glutamyl transferase (GGT) exhibited substrate specificity for c-EC, whereas glutathione reductase did not. The specificities of c-EC and its disulphide form to GGT were comparable to GSH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…P. vulgaris is known to produce γ-glutamyl dipeptides (Giada et al, 1998), but γ-GC was, so far, never found as the dominant LMW thiol/disulphide couple in seeds of 73 investigated species of Leguminosae (Colville et al, 2015). Although considered more as a GSH precursor than antioxidant, γ-GC has a γ-glutamyl moiety coupled to cysteine, enabling this dipeptide to be a substrate to glutathione peroxidase and glutathione transferase (Quintana-Cabrera et al, 2012; Muraoka et al, 2021). Evidently in all species, E γGCCGγ/2γGC parallels E GSSG/2GSH , indicating that both are equally responding to the given seed redox environment and buffering ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…P. vulgaris is known to produce γ-glutamyl dipeptides (Giada et al, 1998), but γ-GC was, so far, never found as the dominant LMW thiol/disulphide couple in seeds of 73 investigated species of Leguminosae (Colville et al, 2015). Although considered more as a GSH precursor than antioxidant, γ-GC has a γ-glutamyl moiety coupled to cysteine, enabling this dipeptide to be a substrate to glutathione peroxidase and glutathione transferase (Quintana-Cabrera et al, 2012; Muraoka et al, 2021). Evidently in all species, E γGCCGγ/2γGC parallels E GSSG/2GSH , indicating that both are equally responding to the given seed redox environment and buffering ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…This can be linked to the inability of the cell to reduce bγ‐GC, as it has been demonstrated that it is not a substrate of GR. [ 39 ] Consequently, the intracellular pool of γ‐GC gradually undergoes oxidation over time into bγ‐GC, particularly during stationary phases when metabolic activity, and thus de novo γ‐GC synthesis, are lower. The third hypothesis for explaining the lower γ‐GC observed after 48 h of growth can be related to Met4 activity.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, γ‐glutamyltranspeptidase (γ‐GT) that normally hydrolyze GSH into glutamate and cysteine‐glycine dipeptide is also active on both γ‐GC and bγ‐GC with the release of glutamate and cysteine, and glycine and cystine (cyst‐cyst), respectively. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, GSH supplementation appears to be a promising target for stroke and neurodegenerative diseases. However, due to the isolation of BBB and the omnipresent γ‐glutamyl transpeptidase, which is responsible for GSH cleavage, GSH supplementation in vitro fails to achieve the ideal effect in neurological protection 253,254 . It was reported in recent years that some stable GSH analogs, prodrugs, and GSH‐coupled nanocarriers, such as ψ‐GSH, l‐cysteine, and γ‐glutamylcysteine, can overcome the disadvantages of GSH administration to achieve the aim of elevating GSH levels in the brain 249,255–259 .…”
Section: Ferroptosis: the Ending Of Iron Overloadmentioning
confidence: 99%